Shelley's broken world : fractured materiality and intermitted song - Coffey, Bysshe Inigo (Liverpool English texts and studies, 2021)
Shelley's Broken World aims to transform the philosophical, scientific, and aesthetic contexts in which Shelley is positioned. It is the first study to refer to and include images of the unpublished 'Marlow List', a record of the books Shelley left behind him on his departure for Italy in 1818. The book represents an exciting new departure in the study of a major Romantic poet.